MECHANISMS AND METHODS OF FINANCING INVESTMENT PROJECTS, THE EXPERIENCE OF IPOTEKABANK OTP GROUP (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article examines the concept and essence of investment lending and project financing, foreign experience of banks in financing investment projects. It is known that financing large enterprises in the country contributes to GDP growth and sustainable economic development. Today, Uzbekistan pays great attention to improving the financial and banking sector, banks with a state share are on the way to privatization. International financial institutions such as the International Finance Corporation (IFC), the European Bank for Reconstruction and Development (EBRD) and the Asian Development Bank (ADB) are involved in the process of privatization of the banking sector. In this study, the possibilities of applying foreign experience in financing investment projects were studied.